Effect Of Electromagnetic Field On Living Structures And Its Importance In Diagnostics And Therapy - I.B. Zuparov (Genius Journals, 2024)
Effect of Electromagnetic Field on Living Structures: Electromagnetic fields can be generated by living structures. The influence of electric and magnetic fields can restore interactions within these structures. Electromagnetic radiation (EMR) and its effects can cause damage in the processes of living structures. Diagnostics and Therapy: Electromagnetic fields are widely used in diagnostics and treatment areas. For example, MRI (Magnetic Resonance Imaging) devices use electromagnetic fields to correct abnormalities and identify changes in the body. Electromagnetic therapy, on the other hand, uses infrared radiation and radiowaves to treat patients. Importance: Electromagnetic fields affect living structures and have the potential to be used in diagnostics and treatment. Through these methods, various diseases and conditions in the body can be identified and treated.
Keywords: Electromagnetic; therapy; diseases; identified